Development of Refractive Parameters in 3- to 6-Year-Old Children and Its Application in Myopia Prediction and Intervention Guidance. (16th December 2021) - Zhang, Ya; Su, Ming; Liu, Hua; Song, Yanxia; Liu, Jing; Sun, Huihui; Wu, Xueya; Yang, Xiaoge; Qi, Liqin; Du, Feifan; Liu, Lili; Chen, Lu; et al.
Abstract : Objective . To investigate refractive development and prevalence of myopia in children aged 3-6 years in Hebei Province, China, and to explore the developmental law of refraction, so as to clinically guide the prediction and intervention of myopia. Methods . In May 2019, a total of 6120 people were inspected in 68 kindergartens in 11 cities in Hebei Province. Child refractive refraction was checked under noncycloplegia using a handheld binocular vision screener (SW-800, SUOER, Tianjin, China). Axial length (AL) and corneal radius of curvature (CR) were measured using an ocular biometry (IOLMaster 500, Carl Zeiss, Germany). Myopia was defined as spherical equivalent SE ≤ − 0.75   D . Results . A total of 5506 children aged 3-6 years met the criteria and were included in the statistical analysis. The prevalence of myopia was 3.49% (1.93% at age 3, 2.90% at age 4, 3.78% at age 5, and 3.88% at age 6). Overall, the mean SE was + 0.67 ± 1.05   D (+ 0.81 ± 1.00   D at age 3, + 0.79 ± 1.05   D at age 4, + 0.67 ± 1.08   D at age 5, and + 0.13 ± 1.01   D at age 6); the mean CR was 7.76 ± 0.26   mm (7.78 ± 0.26   mm at age3, 7.75 ± 0.25   mm at age 4, 7.77 ± 0.26   mm at age 5, and 7.76 ± 0.25   mm at age 6); the mean AL was 22.31 ± 0.73   mm (21.98 ± 0.63   mm at age 3, 22.12 ± 0.69   mm at age 4, 22.34 ± 0.73   mm at age 5, and 22.49 ± 0.73   mm at age 6). Conclusions . Prevalence of myopia increases with age in children aged 3-6 years in Hebei, China. With the increase of age, CR is basically stable, and AL increases gradually. AL/CR, which is closely related to SE, can be used as an indicator to predict myopia and guide clinical work.